2015
DOI: 10.5114/wiitm.2014.47764
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bariatric surgery on nutritional status of patients.

Abstract: IntroductionCurrently, surgical treatment is considered to be the most efficient method of dealing with morbid obesity.AimTo evaluate changes in nutritional status after surgical treatment of obesity in the early postoperative period.Material and methodsThe study included 50 patients (30 women and 20 men) treated surgically due to morbid obesity. During the preliminary visit and during control visits measurements of body mass, height, and waist and hip circumference were conducted. Also, analysis of body conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 32 publications
0
15
0
2
Order By: Relevance
“…With the contribution to the development of general surgery, a number of operative techniques for obesity treatment were invented and a new branch of surgery has been created: bariatric surgery. Nowadays, bariatric surgery is scientifically proven to be the most effective method in curing not only obesity, but also accompanying metabolic disorders and other diseases related to obesity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…With the contribution to the development of general surgery, a number of operative techniques for obesity treatment were invented and a new branch of surgery has been created: bariatric surgery. Nowadays, bariatric surgery is scientifically proven to be the most effective method in curing not only obesity, but also accompanying metabolic disorders and other diseases related to obesity [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the positive effects of modified bariatric surgery procedures in the treatment of non-obese T2DM patients. Therefore, bariatric surgery is also referred to as metabolic surgery because of its results ranging from weight loss to metabolic control, especially in patients with T2DM [ 3 , 4 ]. Currently, T2DM can be considered as a gastrointestinal disease that can be treated surgically, but there is no consensus yet on the criteria of patient selection as various techniques using different mechanisms have different remission rates.…”
Section: Introductionmentioning
confidence: 99%
“…Sleeve gastrectomy (SG) and Roux-Y gastric bypass (RYGB) are currently the most popular bariatric procedures in Poland [ 8 ]. These procedures support a significant reduction of body mass, BMI and waist and hip circumference [ 9 ]. Considering the increasing popularity of minimally invasive surgery, most of the mentioned procedures are performed via laparoscopy.…”
Section: Discussionmentioning
confidence: 99%